2012
DOI: 10.1097/aog.0b013e31825da13e
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned in Physician Reentry

Abstract: We describe our early experience with two physicians who successfully completed an obstetrics and gynecology physician reentry program. A 10-step program using an individualized curriculum in a supervised preceptorship is tailored to the candidate's anticipated practice. A reentry curriculum is devised for the candidate based on the advances in the field since they left practice and Accreditation Council for Graduate Medical Education (ACGME) competencies for resident education. The program culminates with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Although 6 years of experience in a northeastern university hospital with 9 graduates of differing backgrounds and durations of inactivity does not represent all returning physicians’ needs or all reentry programs across the United States, Drexel's approach and our practical experience, viewed alongside work done by other programs, can provide an initial guide for the growing field of obstetrics‐gynecology physician reentry in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although 6 years of experience in a northeastern university hospital with 9 graduates of differing backgrounds and durations of inactivity does not represent all returning physicians’ needs or all reentry programs across the United States, Drexel's approach and our practical experience, viewed alongside work done by other programs, can provide an initial guide for the growing field of obstetrics‐gynecology physician reentry in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Although a few studies have been published on physician reeducation, none provides long‐term follow‐up of physicians who have completed these programs. Nor have any studies reported on physicians’ perspectives about these programs or their assessments of whether the programs prepared them for returning to clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, reports of a small number of OB-GYN re-entry programs already exist. [47][48][49] Delaying Retirement A steady retirement of baby boomer ACOG fellows will compound the projected increased demands on women's health care. While the usual age range of retirement from clinical practice is wide (interquartile range, 59-69 years), OB-GYNs are more inclined to retire slightly earlier than other specialists.…”
Section: Establishing Physician Re-entrymentioning
confidence: 98%
“…3 The importance of the physician reentry issue will be felt by many hospital systems in the near future, when physicians apply for clinical privileges after an extended period of inactivity. When returning to practice, the Diplomate simply notifies the American Board of Obstetrics and Gynecology, and the "not currently in practice" designation is removed.…”
Section: Maintain Active Board Certification the Americanmentioning
confidence: 99%